PENINGKATAN KUALITAS HIDUP PASIEN BRACHIALIS PLEXUS INJURY MELALUI PENDAMPINGAN KEWIRAUSAHAAN - Febri Arifiati, Retna; Sri Wahyuni, Endang (Tahta Media Group, 2024)
Brachial Plexus Injury is a severe peripheral nerve injury that affects the upper extremities, resulting in functional damage and physical disability. Patients with this condition will experience functional limitations in the upper limbs due to a decrease in joint range of motion and muscle strength, thereby affecting productivity. The aim of this research is to determine the improvement in the quality of life of Brachial Plexus Injury Patients through Entrepreneurship Assistance in the Brachial Plexus Injury community. Research Method: This research uses a quantitative descriptive research design. The research was conducted in the Brachialis Plexus Injury community with a sample size of 25 patients using probability sampling techniques with simple random sampling. The instruments used were questionnaires about entrepreneurial intentions, entrepreneurial personality, family support and quality of life. The analysis test used is the multiple linear regression assumption test. Research Results: There is an influence of entrepreneurial mentoring including family support, entrepreneurial intentions, entrepreneurial personality on the quality of life. The F count results are 17.045 with a significance of 0.000. It is known that the G table value is 3.08 because the calculated F value > F table means HO is rejected and Ha is accepted, meaning that there is a significant influence between entrepreneurial assistance on the quality of life of patients with Brachial Plexus Injury conditions. There is a correlation between the variables Family support (X1), Entrepreneurial Personality (X2), Entrepreneurial intentions, with a significance value of 0.000. This means that the significance value of the three variables is smaller than 0.05 or in other words 0.000 > 0.05. So it can be concluded that there is a correlation. To see the level of closeness of the relationship, it can be seen from the R Square of 0.709, which is strongly correlated (according to the rules, if the value is 0.61 to 0.80, it is in the strong correlation category). Conclusion: There is an influence of entrepreneurial assistance including family support, entrepreneurial intentions, entrepreneurial personality on quality of life